2012
DOI: 10.4236/health.2012.48084
|View full text |Cite
|
Sign up to set email alerts
|

Community effects on public health in India: A hierarchical model

Abstract: The data on any aspect of public health, including that on infant mortality, has inbuilt hierarchical structure. Using traditional regression approach in data analysis, i.e., ignoring hierarchical structure, either at micro (individual) or at macro (community) level will be avoiding desired assumption related to independence of records. Accordingly, this may result into distortion in the results due to probable underestimation of standard error of the regression coefficients. To be more specific, an irrelevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 21 publications
4
15
0
Order By: Relevance
“…The data used in the present study are from the National Family Health Survey (NFHS), 1998-1999, conducted for the second time in India. The details about sampling methods, used questionnaires, methods of data collection and all other aspects are already documented [1,6]. The detailed information on antenatal, delivery and postnatal care was obtained for the two most recent births that occurred to eligible women during the three years preceding the survey.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data used in the present study are from the National Family Health Survey (NFHS), 1998-1999, conducted for the second time in India. The details about sampling methods, used questionnaires, methods of data collection and all other aspects are already documented [1,6]. The detailed information on antenatal, delivery and postnatal care was obtained for the two most recent births that occurred to eligible women during the three years preceding the survey.…”
Section: Methodsmentioning
confidence: 99%
“…The detailed information on antenatal, delivery and postnatal care was obtained for the two most recent births that occurred to eligible women during the three years preceding the survey. For analysis, to restore the correct proportion in view of no self-weighting of the sample design, the country-level weight was used [1]. As considered earlier [1], in present analysis also, infant mortality was taken as dependent variable (i.e., child who died before his/her first birthday) in the last three years preceding the survey (0 = alive, died = 1).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both bivariate and multivariate analysis indicate that children born during 2005-2006 and during 1996-99, the hazard risk of infant mortality was less compared to the period 1992-1993. As true in the case of infant mortality in India [27], and earlier study shown that the infant mortality varies by socio-economic and demographic characteristics, and also reveals that those mothers have comparatively lower education whose children are more likely to die before celebrating their first birthday [28]. Earlier studies reveals that the birth order and birth interval of the child significantly associated with mortality [29] and a study on utilization of maternal health care services suggested that higher mortality risk among first order birth could be linked to the early childbearing trends and lower utilization of maternity health care services in developing countries like India [30].…”
Section: Discussionmentioning
confidence: 99%